AI in Communication: Theoretical Perspectives, Ethical Implications, and Emerging Competencies - Aleksandra Mirek-Rogowska; Wojciech Kucza; Krzysztof Gajdka (Communication Today, 2025)
Artificial intelligence (AI) is rapidly transforming communication processes across various sectors, including marketing, education, healthcare, and entertainment. This study explores the theoretical perspectives surrounding AI’s integration into communication, examining how AI-driven tools such as ChatGPT, MidJourney, and Google Gemini are reshaping content creation, personalisation, and human-machine interaction. While AI enhances efficiency and allows for real-time customisation of messages, it also presents ethical challenges related to privacy, data security, and algorithmic bias. By synthesising key academic studies, the study outlines the critical ethical considerations, including the risks of deepfakes and disinformation, and emphasises the need for ethical frameworks to guide responsible AI use. The text also discusses the new digital competencies required to navigate AI-enhanced communication environments, such as AI literacy, data proficiency, and ethical reasoning. Through a systematic literature review, this study contributes to the ongoing discourse on AI’s role in communication by offering a comprehensive theoretical framework that highlights both the opportunities and limitations of AI technologies. Future research should focus on addressing gaps in empirical studies, particularly concerning the long-term impacts of AI on decision-making and the ethical governance of AI-generated content.